2015
DOI: 10.1039/c5ra04353k
|View full text |Cite
|
Sign up to set email alerts
|

PDMS micropillar-based microchip for efficient cancer cell capture

Abstract: We introduce a micropillar-based microfluidic device for efficient and rapid cancer cell capture. The microfluidic chip consists of two linear arrays of micropillars integrated with a herringbones flow-derived microstructure, and the separation distance between two adjacent micropillars is similar to the size of tumor cells. Cancer cells can be forced to come into contact with the micro-columns and are then captured by specific immune antibody-antigen interactions. Both previously published data and new availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The microchip mold with different heights was fabricated on a silicone wafer using an SU8 3050 photoresist through a two-step alignment photolithography process according to a previous study. [34] Then, PDMS (RTV615) (base-polymer: cross-linker-10:1) was poured onto the mold. After degassing by a vacuum pump, the PDMS was curved at 80 C for 1 h on a heating stage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The microchip mold with different heights was fabricated on a silicone wafer using an SU8 3050 photoresist through a two-step alignment photolithography process according to a previous study. [34] Then, PDMS (RTV615) (base-polymer: cross-linker-10:1) was poured onto the mold. After degassing by a vacuum pump, the PDMS was curved at 80 C for 1 h on a heating stage.…”
Section: Methodsmentioning
confidence: 99%
“…The distance between the two electrodes was 1.0 mm. The microchip mold with different heights was fabricated on a silicone wafer using an SU8 3050 photoresist through a two‐step alignment photolithography process according to a previous study . Then, PDMS (RTV615) (base‐polymer:cross‐linker—10:1) was poured onto the mold.…”
Section: Methodsmentioning
confidence: 99%
“…The number of the CTCs can be utilized as an indicator of clinical progression . Because of its critical importance, many methods based on cell or nucleus sizes, nanosized surface structure, and special antigen have been developed to capture CTCs. However, few studies on the deformation of the CTCs have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…On the other, the creation of micro/nanostructures on the substrate surface enhances the cell adhesivity by providing structural features of a suitable size for cell protein attachment 18 , although the optimal size is dependent on the cell characteristics 19 , 20 . Generally, a feature size around 100 nm is advantageous for cell adhesion, and the cell compartments interact with the surface features positively 21 .The combination of both chemical and physical methods has also been widely explored; for example, roughened surfaces with micro/nano features have been created by photolithography processing or photonic crystal assembly, followed by the structured surface being coated with chemicals to improve biological compatibility 22 24 . Previous studies have demonstrated that the combined use of both physical and chemical methods enhances cell adhesivity and proliferation.…”
Section: Introductionmentioning
confidence: 99%